Synthesis, structure and magnetic properties of La 3Co 2SbO 9: A double perovskite with competing antiferromagnetic and ferromagnetic interactions - Franco, Diego Gaspar (2012)
The synthesis, structural characterization, and magnetic properties of La 3Co 2SbO 9 double perovskite are reported. The crystal structure has been refined by X-ray and neutron powder diffraction data in the monoclinic space group P2 1/n. Co 2 and Sb 5 have the maximum order allowed for the La 3Co 2SbO 9 stoichiometry. Rietveld refinements of powder neutron diffraction data show that at room temperature the cell parameters are a=5.6274(2) Å, b=5.6842(2) Å, c=7.9748(2) Å and β=89.999(3)°. Magnetization measurements indicate the presence of ferromagnetic correlations with T C=55 K attributed to the exchange interactions for non-linear Co 2-O-Sb 5-O-Co 2 paths. The effective magnetic moment obtained experimentally is μ exp=4.38 μ B (per mol Co 2), between the theoretical one for spin only (3.87 μ B) and spin-orbit value (6.63 μ B), indicating partially unquenched contribution. The low magnetization value at high magnetic field and low temperature (1 μ B/f.u., 5 T and 5 K) and the difference between ZFC and FC magnetization curves (at 5 kOe) indicate that the ferromagnetism do not reach a long range order and that the material has an important magnetic frustration.